1974
DOI: 10.1017/s0021859600026939
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of natural cross-fertilization in a composite cross of barley grown in Scotland

Abstract: The frequency of natural crossing in 1972 was estimated, in two subsets of a composite cross grown in F e in Nairn and in Fife, as 2-61 ±0-25% and 4-59 ±0-35% respectively. The estimated inbreeding coefficients of the parental generations were less than would be expected if all types of pollination were equally fertile and gave equally fertile offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…In addition, under cool and moist conditions, higher outcrossing rates may be caused by extended pollen viability (Hammer 1977;Lansac et al 1994;Gupta et al 2000). Our results agree with the findings of Giles et al (1974), Brown et al (1978) and Chaudhary et al (1980) who showed that cool and moist conditions promote outcrossing in barley.…”
Section: Influence Of Climatic Conditionssupporting
confidence: 93%
“…In addition, under cool and moist conditions, higher outcrossing rates may be caused by extended pollen viability (Hammer 1977;Lansac et al 1994;Gupta et al 2000). Our results agree with the findings of Giles et al (1974), Brown et al (1978) and Chaudhary et al (1980) who showed that cool and moist conditions promote outcrossing in barley.…”
Section: Influence Of Climatic Conditionssupporting
confidence: 93%
“…was negative in d l cases, which tends to support the earlier observation that low temperature promotes natural outcrossing in barley (Giles et al, 1974). However, this generalization cannot be made in the presence of field level moisture stress, as the rate of outcrossing at Davis, California was higher than for the dryland population at Saskatoon.…”
Section: Resultssupporting
confidence: 77%
“…vulgare) has many of the hallmarks known to be associated with a high level of LD. Its effective recombination rate is dramatically reduced by its predominantly inbreeding habit, with an estimated outcrossing rate of 5% in winter barley and ,0.5% in spring barley (Giles et al 1974;Doll 1987;Abdel-Ghani et al 2005). Domestication and intensive selection have introduced major bottlenecks in genetic variation, and these are thought to be largely responsible for the perceived narrowness of the modern gene pool (Badr et al 2000;Russell et al 2000;Matus and Hayes 2002).…”
mentioning
confidence: 99%